An omproved reaction rate formulation for charged-particle induced thermonuclear reaction of [sup 2]H(d,γ)[sup 4]He - Abdul Aziz, Azni; Yusof, Norhasliza; Idris, Mahirah; Abu Kassim, Hasan (American Institute of Physics, 2011)
The reaction rate formula utilized in compilations such as the Nuclear Astrophysics Compilation of Reaction Rates (NACRE) uses low energy approximation due to temperatures in stars are in the region of a few keVs. Most nuclear reaction experiments were done in MeV range and the interior temperatures of massive stars are ~ 10^9 K. Hence an improved formulation for calculating the nuclear reaction rate that is applicable to high temperatures is discussed in this work. The exact tunneling probability that is applicable for all energies is obtained by solving the Schrödinger equation. This yields an enhanced expression for the astrophysical S-factor for calculating the thermonuclear reaction rate at high temperature. The thermonuclear reaction rate from this work is applied to the 2H(d,γ)4 Keywords: coulomb energies, interaction and reaction cross sections, fusion reactions He reaction and is compared with the NACRE compilation. This improved reaction rate can be included in the nuclear reaction network in a Big Bang nucleosynthesis (BBN) code or a stellar nuclear network code.